Failure of Myanmar's Democratic Transition - Evisia Novitri; Supriyadi Supriyadi; Adhiningasih Prabhawati (University of Jember, 2023)
Myanmar is one of the countries that carried out military coups several times from 1962 to 2021. Although known as an authoritative ruler, the military junta has carried out more democratic policies, such as opening space for press freedom and holding Myanmar‘s election which allowed the participation of a pro-democratic party namely the NLD Party. However, the military junta suddenly staged a military coup in 2021. In previous years, Myanmar's military junta attempted to make a democratic transition. This raises the question of what factors caused the democratic transition in Myanmar to fail, despite previous positive results. The phenomenon of democratic transition in Myanmar will be analyzed using democratic transition theory, democratization theory, and the concept of civil-military relations. This study uses an approach-explanation approach to determine the failure factors of the democratic transition in Myanmar. Based on the theories, concepts, and research methods used, the failure of the democratic transition in Myanmar occurred due to four factors: The first factor is the democratic transition in Myanmar using the top-down path. The second factor is that the transition is not followed by the installation of democracy. The third factor is that the civil-military relations in Myanmar are included in the category of unbalanced civilian accommodation. The fourth factor, the military afraid of Aung San Suu Kyi succeeded in amending the 2008 constitution which will remove military privileges.